Cervical cancer surgery: Current state of affairs - Fan Chun Yang; Wei Huang; Weihong Yang; Jie Liu; Guihai Ai; Ning Luo; Jing Guo; Peng Teng Chua; Zhongping Cheng (Wolters Kluwer Medknow Publications, 2021)
Cervical cancer surgery has a history of more than 100-years whereby it has transitioned from the open approach to minimally invasive surgery (MIS). From the era of clinical exploration and practice, minimally invasive gynecologic surgeons have never ceased to explore new frontiers in the field of gynecologic surgery. MIS has fewer postoperative complications, including reduction of treatment-related morbidity and length of hospital stay than laparotomy; this forms the mainstay of treatment for early-stage cervical cancer. However, in November 2018, the New England Journal of Medicine had published two clinical studies on cervical cancer surgery (Laparoscopic Approach to Cervical Cancer [LACC]). Following these publications, laparoscopic surgery for early-stage cervical cancer has come under intense scrutiny and negative perceptions. Many studies began to explore the concept of standardized surgery for early-stage cervical cancer. In this article, we performed a review of the history of cervical cancer surgery, outlined the standardization of cervical cancer surgery, and analyzed the current state of affairs revolving around cervical cancer surgery in the post-LACC era.